A Study on the Genetics of Primary Ciliary Dyskinesia - Mohammed T. Alsamri (MDPI AG, 2021)
Primary ciliary dyskinesia (PCD) is a poorly understood disorder. It is primarily autosomal recessive and is prevalent in tribal communities of the United Arab Emirates due to consanguineous marriages. This retrospective study aimed to assess the pathogenicity of the genetic variants of PCD in indigenous patients with significant clinical respiratory problems. Pathogenicity scores of variants obtained from the chart review were consolidated using the Ensembl Variant Effect Predictor. The multidimensional dataset of scores was clustered into three groups based on their pathogenicity. Sequence alignment and the Jensen–Shannon Divergence (JSD) were generated to evaluate the amino acid conservation at the site of the variation. One-hundred and twelve variants of 28 genes linked to PCD were identified in 66 patients. Twenty-two variants were double heterozygous, two triple heterozygous, and seven homozygous. Of the thirteen novel variants, two, c.11839 + 1G > A in dynein, axonemal, heavy chain 11 (DNAH11) and p.Lys92Trpfs in dynein, axonemal, intermediate chain 1 (DNAI1) were associated with dextrocardia with situs inversus, and one, p.Gly21Val in coiled-coil domain-containing protein 40 (CCDC40), with absent inner dynein arms. Homozygous C1orf127:p.Arg113Ter (rs558323413) was also associated with laterality defects in two related patients. The majority of variants were missense involving conserved residues with a median JSD score of 0.747. Homology models of two deleterious variants in the stalk of DNAH11, p.Gly3102Asp and p.Leu3127Arg, revealed structural importance of the conserved glycine and leucine. These results define potentially damaging PCD variants in the region. Future studies, however, are needed to fully comprehend the genetic underpinnings of PCD.